1993
DOI: 10.1091/mbc.4.11.1205
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of NGF-stimulated extracellular matrix invasion by the human melanoma low-affinity p75 neurotrophin receptor: melanoma p75 functions independently of trkA.

Abstract: Although overexpression of the low-affinity p75 neurotrophin receptor (p75NTh) is frequently associated with advanced stages of human melanoma progression, the functional significance of this finding is unknown. We examined whether the degree of cell surface expression of p75NTR in human melanoma cell variants determines their extent of invasion stimulated by nerve growth factor (NGF). Treatment of MeWo melanoma cells or a metastatic spontaneous wheat germ agglutinin-resistant variant subline (70W) of MeWo cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
2

Year Published

1996
1996
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 48 publications
6
93
2
Order By: Relevance
“…These results were related to protein NTR content in these cells by performing NTR (p75 NTR and TrkC) immunoprecipitation studies, as previously reported (Herrmann et al, 1993). Figure 1 shows the results of a representative Western blot analysis using c-Src and c-Yes antibodies designed to determine c-Src and c-Yes levels in human parental MeWo and its two variants, 3 S 5 and 70W, possessing di erent and contrasting metastatic capabilities (Ishikawa et al, 1988a,b).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…These results were related to protein NTR content in these cells by performing NTR (p75 NTR and TrkC) immunoprecipitation studies, as previously reported (Herrmann et al, 1993). Figure 1 shows the results of a representative Western blot analysis using c-Src and c-Yes antibodies designed to determine c-Src and c-Yes levels in human parental MeWo and its two variants, 3 S 5 and 70W, possessing di erent and contrasting metastatic capabilities (Ishikawa et al, 1988a,b).…”
Section: Resultssupporting
confidence: 79%
“…In the present report, we show that the activity and level of c-Yes, but not c-Src, are upregulated in human brain-metastatic 70W cells, that such activity correlates with the metastatic potential of human melanoma cells, that stimulation of c-Yes by select NT correlates with their capacity to act as brain-invasive factors and with increased expression of p75 NTR and TrkC present in these cells (Marchetti et al, , 1995Herrmann et al, 1993). These results suggest a speci®c role of NRPTKs activation in melanomas, and the potential involvement of NRPTKs in the development of brain metastases.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations